An Impact of the Euro Adoption on the International Trade of New EMU Members: the Lithuanian Case - Gražina Startienė; Daiva Dumčiuvienė; Alina Stundžienė; Andrius Januškevičius (Entrepreneurial Business and Economics Review)
Objective: This article aims to assess the impact of the euro on the Lithuanian international trade by detecting the changes of the relevant economic indicators before and after the country’s entry into the Eurozone. Research Design & Methods: The research is based on the gravity model of trade. The parameters of the model show elasticity of trade in respect of the determinants that are incorporated. The parameters of the model are estimated by the panel least square method. Findings: The results obtained using the gravity model showed that the euro has significantly increased the Lithuanian intra-Eurozone trade, with an effect of 23-44%. The size of effect depends on the model specification. Implications & Recommendations: The results can be used to discuss the positive impact of a common currency on the economics of a country. It is important for those EU members which still have not adopted the euro. Contribution & Value Added: Previous studies showed a different impact of the common currency on trade volumes, and the results depend on many factors, i.e. country, period, method and so on. This research supplements previous studies and reveals that the euro adoption has a positive impact on specifically Lithuanian trade volumes.